Launching a Blue Economy: crucial first steps in designing a contextually sensitive and coherent approach. Issue 3 (4th May 2021) - Voyer, Michelle; Quirk, Genevieve; Farmery, Anna K.; Kajlich, Lana; Warner, Robin
ABSTRACT: The Blue Economy is an emerging framework through which sustainable development is being pursued within the oceans. To date there is limited guidance into how a Blue Economy should be enacted. We propose four initial steps in the development of Blue Economy policies and plans. Firstly, we argue for early deliberation over what is meant by the Blue Economy within the relevant context. Secondly, consideration of the sectors that make up a Blue Economy should be articulated. Thirdly, we argue that Blue Economy plans should aim to be coherent within the existing policy framework. Therefore, an assessment is required of the existing policy settings for the relevant marine and coastal sectors, and the degree to which they are already coherent, or 'mutually consistent' with each other. Finally, a contextually sensitive and coherent Blue Economy policy can be designed which plugs policy gaps and adds value to the existing situation. We test the application of these four steps in two different case study areas, a region of Australia and Timor Leste. Despite substantial differences in context, the process identified ways in which Blue Economy policies could add value to existing governance arrangements in both settings.